Voice disorders in the elderly: A national database study. (17th August 2015) - Roy, Nelson; Kim, Jaewhan; Courey, Mark; Cohen, Seth M.
Abstract : Objectives/Hypothesis: To determine the type, frequency, and factors associated with voice disorders in the elderly. Study Design: Retrospective analysis of data from a large national administrative US claims database. Methods: Elderly outpatients (>65 years old) with a laryngeal/voice disorder (LVD) diagnosis based on International Classification of Diseases, Ninth Revision, Clinical Modification codes from January 1, 2004 to December 31, 2008, seen by an otolaryngologist or primary care physician (PCP) were included. Data regarding age, gender, comorbid conditions, geographic location, employment history, and type of physician providing the diagnosis were collected, and multiple logistic regression was used to determine the influence of these factors in otolaryngologist‐determined LVD diagnoses. Results: Of the almost 55 million individuals in the database, 60, 773 unique patients (mean age = 74.9 years, standard deviation = 6.6 years, range = 65–105 years) had an encounter with a PCP or otolaryngologist and received an LVD diagnosis. The most frequent diagnoses overall were acute and chronic laryngitis, nonspecific dysphonia, and benign vocal fold lesions. PCPs more commonly diagnosed acute laryngitis, whereas otolaryngologists more commonly diagnosed nonspecific dysphonia and laryngeal changes/lesions. In the otolaryngology group, odds of nonspecific dysphonia and vocal fold paralysis/paresis diagnoses increased with advancing age, whereas benign laryngeal pathology, and acute and chronic laryngitis decreased. As compared to men, women had lower odds of paralysis/paresis and laryngeal cancer but higher odds of acute laryngitis and nonspecific dysphonia. Odds of specific LVDs also varied depending upon comorbid conditions and geographic location. Conclusions: Age, gender, comorbid conditions, geographic location, and physician type were significantly associated with specific LVD diagnoses within the elderly. Level of Evidence: 4 Laryngoscope, 126:421–428, 2016